Language, Identity, and Emotion in Wuthering Heights: A Critical Analysis (Journal of NELTA Gandaki, 2025)
This study critically analyzes the interconnected relationship among language, identity, and emotion in Wuthering Heights by Emily Brontë, to examine how Brontë's use of language shapes character identities and emotional expression, particularly in the context of social class, gender, and psychological depth. The purpose is to unveil how linguistic style, including dialects, narrative structure, and emotional tone, contributes to the construction of identities within the novel’s gothic framework. The methodology adopts a qualitative textual analysis that is exploratory in nature, aiming to reveal new interpretations rather than test pre-set hypotheses. This analysis applies Reader-Response Theory and Psychoanalytic Criticism to examine the language patterns of key characters such as Heathcliff, Catherine Earnshaw, Edgar Linton, and others. This approach allows for an interpretive understanding of how emotions like love, rage, and alienation are conveyed and how they influence identity formation and transformation across generations. While Wuthering Heights has been widely studied for its gothic and romantic elements, there is a research gap in comprehensively analyzing how language specifically mediates identity and emotion in the narrative. This study contributes to filling that gap by linking linguistic expression with psychological and social identity. Through this lens, the paper highlights how Brontë’s layered narrative voices and emotional intensity offer insights into the entanglement of language, selfhood, and human feeling, thereby enriching the discourse on literary identity studies.